THE INFLUENCE OF PRODUCT VARIATION AND SALES PROMOTION TOWARD SALES PROMOTION (CASE STUDY OF PT MUARA KRAKATAU II) - Devi Larasati; Riyadi Riyadi; Umar Farouk (Politeknik Negeri Semarang, 2018)
The purpose of this research is to analyze the influence of product variation and sales promotion toward sales performance of PT Muara Krakatau II both partially and simultaneously. The Independent variables studied in this research are product variation and sales promotion, meanwhile the sales performance is as the dependent variable. This is a quantitative research using secondary data in the form of time series in quarterly starting at 2015-2017. The analysis method used in this research are classic assumption test consist of (normality, multicollinearity, heterocedasticity, autocorrelation, and linearity test), t-test,F-test, multiple linier regression test and coefficient of determination (R2). The result of structural equation is Sales Performance is 0,806 Product Variation + 0,331 Sales Promotion. The result of significant parameter t-Test stated that both independent variables namely Product Variation and Sales Promotion partially has a significant influence on Sales Performance. The result of F-Test shows that simultaneously there is a significant influence among Product Variation and Sales Promotion on Sales Performance. The coefficient Determination (Adjusted R2 value) of the model is (0,883) 88,3%, it means that the contribution of Product Variation and Sales Promotion to Sales Performance of PT Muara Krakatau II is 88,3%. The rest of the contribution 11,7% is affected by other variables that are not describes in this research.